Bactericidal effect of trypan blue and fluorescein sodium in ophthalmic practice - Malhotra, S; Nirmalijit, Kaur; Mehta, DK (Nepalese Journal of Ophthalmology, 2012)
Objective: Trypan blue and fluorescein sodium are two commonly used dyes in ophthalmic practice. The staining of anterior lens capsule is achieved using trypan blue while fluorescein finds its application in fluorescent angiography. We assessed the ‘in vitro’ bactericidal effect of these two agents. Materials and methods: The cidal properties of these two dyes were tested in vitro against thirty representative strains of four commonly isolated bacteria from the eye. The concentration of dyes used were 0.6 mg/ml, 0.1 mg/ml, and 0.05 mg/ml for trypan blue and 20 mg/ml, 10 mg/ml and 5 mg/ml for fluorescein sodium. Result: We found that trypan blue and fluorescein sodium at an optimum concentration of 0.6 mg/ml and 20 mg/ml respectively could produce a significant fall (p < .05) in the bacterial count of representative Gram positive and Gram negative bacteria. Conclusion: The use of prophylactic antibiotics/antiseptic eye drops can be avoided if these two dyes are used at an optimum bactericidal concentration but side effects of the same at these concentrations need to be kept in mind. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5856 NEPJOPH 2012; 4(1): 80-83